2001
DOI: 10.1038/35078615
|View full text |Cite
|
Sign up to set email alerts
|

From fixed to FRAP: measuring protein mobility and activity in living cells

Abstract: Experiments with fluorescence recovery after photobleaching (FRAP) started 30 years ago to visualize the lateral mobility and dynamics of fluorescent proteins in living cells. Its popularity increased when non-invasive fluorescent tagging became possible with the green fluorescent protein (GFP). Many researchers use GFP to study the localization of fusion proteins in fixed or living cells, but the same fluorescent proteins can also be used to study protein mobility in living cells. Here we review the potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
485
1
4

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 594 publications
(498 citation statements)
references
References 29 publications
8
485
1
4
Order By: Relevance
“…Fluorescence recovery was recorded over 5 min at 1 frame every 4 s. To control for movement in and out of focus, multiple regions of interest (ROI) were selected in nonphotobleached regions; only samples for which intensities within control ROIs remained steady throughout the FRAP experiment were used. Recovery data were further analyzed using Prism software (GraphPad, La Jolla, CA): mobile fraction was calculated as previously described (Reits and Neefjes, 2001 …”
Section: Fluorescence Recovery After Photobleaching (Frap)mentioning
confidence: 99%
“…Fluorescence recovery was recorded over 5 min at 1 frame every 4 s. To control for movement in and out of focus, multiple regions of interest (ROI) were selected in nonphotobleached regions; only samples for which intensities within control ROIs remained steady throughout the FRAP experiment were used. Recovery data were further analyzed using Prism software (GraphPad, La Jolla, CA): mobile fraction was calculated as previously described (Reits and Neefjes, 2001 …”
Section: Fluorescence Recovery After Photobleaching (Frap)mentioning
confidence: 99%
“…Several investigations have followed subcellular trafficking of MR and GR in living cells using green fluorescent protein (GFP) and its color variants (Htun et al, 1996;Fejes-Toth et al, 1998;Nishi et al, 2001;DeFranco, 2002). Furthermore, McNally et al (2000) showed that the hormone-occupied GR undergoes a rapid exchange between chromatin and the nucleoplasmic compartment by using the fluorescent recovery after photobleaching technique (Reits and Neefjes, 2001). We focused on the spatiotemporal-specific interactions between GR and MR in living cells.…”
Section: Introductionmentioning
confidence: 99%
“…In bulk liquids, viscosity and diffusion constant are inversely proportional to each other. To investigate this relationship in two-dimensional membranes, and gain additional information on the effects of cholesterol, fluorescence recovery after photobleaching (FRAP) (Axelrod et al, 1976;Edidin et al, 1976;Reits and Neefjes, 2001) was used to measure the lateral diffusion of a lipid analog DiIC 12 .…”
Section: Introductionmentioning
confidence: 99%